Fast software encryption : 21st International Workshop, FSE 2014, London, UK, March 3-5, 2014. Revised selected papers /: 21st International Workshop, FSE 2014, London, UK, March 3-5, 2014. Revised selected papers. (2015) - Unknown
No abstract available